Social network analysis in the science of groups: Cross-sectional and longitudinal applications for studying intra- and intergroup behavior - Wölfer, R; Faber, NS; Hewstone, M (American Psychological Association, 2015)
Social scientists increasingly recognize the potential of social network analysis, which enriches the explanation of human behavior by explicitly taking its social structure into account. In particular for the science of groups, social network analysis has reached a point of analytic refinement that makes it a valuable tool for investigating some of the central mechanisms that underlie intra- and intergroup behavior. The present article highlights the general relevance of this scientific approach and describes the background, generation, and application of cross-sectional as well as longitudinal network statistics that are of specific interest to group researchers. In doing so, we aim to provide a general introduction for researchers new to this approach, while demonstrating the potential and limitations of social network analysis for different areas in this field.